Demography of Early Entrepreneurship: Experience of Different Countries in Recent Years - Pinkovetskaia, Iuliia; Nikitina, Irina; Gromova, Tatiana (Journal of History Culture and Art Research, 2019)
The relevance of the study is due to the important role played by small and medium-sized businesses in the vast majority of modern national economies. The aim of the study is to assess the indicators describing the share of early-stage entrepreneurs belonging to five age groups in the total population of the respective age groups in different countries. The baseline data were the results of the Global Entrepreneurship Monitor project for 2018 among 48 countries and for 2017 among 54 countries. The estimation of differentiation of the considered indicators was carried out with the use of mathematical models representing density functions of normal distribution. The test showed that the developed functions well approximate the empirical data. On the basis of these functions, the average values and intervals of changes in the rates of early-stage entrepreneurial activity for most countries were determined. The study showed that the largest share of early-stage entrepreneurs in the total population is typical for people aged 25 to 44 years. The share of start-up entrepreneurs belonging to the group from 55 to 64 years is significantly lower. The study allowed to identify the countries, which are characterized by high and low values of indicators of early-stage entrepreneurial activity for these age groups.